Kemampuan Adaptasi Positif Melalui Resiliensi - Intan Mutiara Mir’atannisa; Nandang Rusmana; Nandang Budiman (Journal of Innovative Counseling : Theory, Practice, and Research, 2019)
The purpose of this study is to understand how important resilience as positif adaptation. This paper focuses on describing resilience, especially about definition, dimention, factor, and instrument resilience. There are four dimentions that can help people to build resilience. These four dimention are determination, endurance, adaptability, and recuperability. Resilience is influenced by individual, family, and social environmental factors. The results of this study can use to become a reference for the future researchers.